The golden teeth and dental inlays of the Visayans from the Philippine expedition collection of the University of Michigan - Estrella, Victor (2021)
The study re-examines the evidence and interpretation of the ancient custom of gold dental inlaying in the Visayas. The teeth with gold inlays and perforations analyzed in this paper are from the Philippine Collection of the University of Michigan that were recovered through an expedition by Carl Guthe in the 1920s in central Philippine sites. Substantiating archaeological data with historical and ethnographic accounts. I argue that these gold dental inlays go beyond ornamentation. The explanation for such a custom lies in the early Visayan population's belief that gold, a msytical metal, transformed teeth into an important body part that had a spiritual dimension.
Keywords: Anthropology; Archaeological museums and collections; Tradition and beliefs; Dental materials